PERAN PROGRAM PENDIDIKAN BERBASIS PESANTREN DALAM MEMPERKUAT KARAKTER RELIGIUS PESERTA DIDIK - atiqoh mufidah; Syamsul Ghufron; muhammad thamrin hidayat; suharmono kasiyun (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
The purpose of this study is to describe the educational program, religious character, and the role of the education program in strengthening religious character in MI Al Fithrah Surabaya. This research is classified as a qualitative descriptive study. The data sources of this study were the principal, vice principal, and class teachers at MI Al Fithrah. Research data were collected by interview technique and documentation using interview guide instruments. Data analysis uses data reduction, data display, and verification. The results showed that the pesantren-based education program at MI Al-Fithrah included the morality curriculum, reading and writing books in the style of Javanese meaning, 8C character education, everyday with the Qur'an, BIMTAQ (Faith and Taqwa Guidance), and extracurricular activities. The religious character is divided into three aspects, namely the religious character of the relationship with God (morning sunnah prayers, pray for parents, read the Qur'an, pray the dluhur in congregation, the Prophet's birthday, and the pilgrimage of Qubur), fellow humans (being polite to the teacher , respect for others, get along well with fellow friends, and friday shodaqoh), and the environment (clean the environment, throw garbage in its place, and plant live pharmacy plants). The education program in MI Al Fithrah has a role in strengthening the religious character of students, with the existence of pesantren education that teaches about various religious knowledge. The strategy used is an exemplary strategy, habituation, learning, reinforcement, assistance, and assessment.